Policy recommendations for improving health literacy: based on European Health Literacy Survey 2019. (20th October 2021) - Dietscher, C; Le, C; Telo de Arriaga, M; Schaeffer, D; Drapkina, O; De Gani, S
Abstract: The European network on Measuring Population and Organizational Health Literacy (M-POHL) was founded in 2018 under the umbrella of the European Health Information Initiative (EHII) of the World Health Organization - Regional Office for Europe. Health literacy (HL) is increasingly recognized as a critical determinant, mediator or moderator of health, and large parts of populations have been shown to have limited HL. Therefore, it is one of the aims of M-POHL to install international comparative population HL surveys at regular intervals. These can provide a valuable and valid basis for developing evidence-informed recommendations for policy, research and practice in the field of HL. To meet this purpose, M-POHL brings together experts from research and policy. Following up on the first European HL survey (HLS-EU), the first project of M-POHL was the international HLS19 survey, with 17 participating countries from the WHO European region. In addition to general population HL, the survey also covered specific HL's such as digital, communication, navigation, and vaccination HL. Despite the obstacles posed by the Corona pandemic, the survey could be administered, and an international comparative report was prepared by the HLS19 project consortium. On this basis, M-POHL will hold two workshops in June and August 2021 to develop resulting recommendations for policy and research in Europe. It is expected that these recommendations will a. o. focus on: population groups in most need of support in their HL; how to improve different dimensions of HL (such as finding, understanding, assessing, and applying relevant health information); HL as applied to health care, disease prevention, and health promotion; and aspects relating to the specific HL's measured. The presentation will describe the process of development, and give an overview of the M-POHL recommendations.